A fuzzy Fine-Kinney-based risk evaluation approach with extended MULTIMOORA method based on Choquet integral. (November 2018) - Wang, Weizhong; Liu, Xinwang; Qin, Yong
Highlights: The interactions among risk factors is considered in Fine-Kinney approach. An integrated Choquet integral is used to determine the risk parameter weight. An extended MULTIMOORA method is proposed to prioritize risk of hazard. Sensitivity and comparison analysis are conducted to illustrate the new method. Abstract: The Fine-Kinney as a comprehensive and quantitative risk assessment method has been commonly applied to aid in controlling occupational hazards in practice. However, the Fine-Kinney-based risk evaluation approach suffers from the drawbacks of failing to deal with the interaction relationships between risk parameters and determine the risk priority of occupational hazards. The purpose of this paper is to propose a novel Fine-Kinney-based risk evaluation approach combining triangular fuzzy number, MULTIMOORA method and Choquet integral to overcome the limitations in the current Fine-Kinney-based risk evaluation approach. First, the triangular fuzzy number is employed to determine the risk parameters scores in Fine-Kinney approach. Second, the relative preference relation based triangular fuzzy number ranking method is integrated with the Choquet integral to determine importance weights of risk parameters. Third, an extended MULTIMOORA method with Choquet integral is proposed to determine the risk priority order of hazards by considering the interaction relationships between risk parameters. Finally, a case study of ballast tank maintenance is selected to demonstrate the application and feasibility of the proposed hybrid Fine-Kinney-based risk evaluation method, and comparison and sensitivity analysis are also conducted to validate the effectiveness of the new risk assessment model.